What is the tourist landscape? Aspects and features of the concept - Ewa Skowronek; Andrzej Tucki; Edward Huijbens; Marta Jóźwik (Acta Geographica Slovenica, 2018)
This paper will present a systematic review of the main publications for landscape and tourism research in Scopus and polish language databases. These were used to identify papers on landscape and tourism published from January 2003 to September 2013. A total of 382 articles and 37 other sources were identified, but 116 analysed. The analysis, focusing on the explicated relation between landscape and tourism, shows that it is a new but growing concern for geographers, ecologists, and landscape architects contributing to the debate. The result is a veritable smorgasbord of definitions and approaches. The objective of this paper is to systematise the current knowledge on tourism and landscape, review the existing definitions of the term “tourist landscape”, and determine its aspects and components in the context of proper functioning of regions. The paper concludes with a tentative definition of a tourist landscape and proposals for further scholarly research and some policy advice.